Statistical Study of Whistler‐Mode Waves and Expected Pitch Angle Diffusion Rates During Dispersionless Electron Injections. Issue 17 (3rd September 2021) - Ghaffari, R.; Cully, C. M.; Gabrielse, C.
Abstract: Energetic electron injections can generate or amplify electromagnetic waves such as whistler‐mode waves. These waves can resonantly interact with available particles to affect their equatorial pitch angle. This process can be considered as a diffusion that scatters particles into the loss cone. This study investigates whistler‐mode wave generation in conjunction with electron injections using in situ wave measurements by the Time History of Events and Macroscale Interactions during Substorms mission during 2011–2020. We characterize the whistler‐mode wave behavior associated with 733 selected dispersionless electron injections and dipolarizing flux bundles (DFBs). We observe intense wave activity and strong diffusion associated with only the top 5% and 10% of the selected injection events, respectively. We also study the wave activity when there is a sharp rise in the northward component of the magnetic field around the injection time (DFBs). In this case, the generated wave powers increase, and the power change is at least two times greater than non‐DFB injections. Plain Language Summary: During some space weather events, energetic electrons are transported toward the Earth and alter the particle population in the near‐Earth space environment. This change in particle distribution may cause the generation of electromagnetic waves in the region. These generated waves can interact with the available particles and transfer energy to them to affect the system dynamics. These affected particles can be precipitated into the atmosphere and have several impacts on the Earth, such as interruption in radio communication. This study is about one specific type of space event called "energetic electron injection." We investigate typical wave power in conjunction with Electron Injections to better understand possible wave‐particle interactions and their impacts on the near‐Earth space environment dynamics during these events. We show that only very few of these events are associated with strong wave generation. Key Points: Analyzing 733 dispersionless electron injections, only 5% show an increase in whistler‐mode wave power by more than an order of magnitude Roughly, 10% of the analyzed injections show a measurable increase in diffusion rate Greater increases in wave power are observed when the injection is coincident with magnetic field dipolarization